Quantitative assessment of tumor-infiltrating lymphocytes in mismatch repair proficient colon cancer. (1st January 2020) - Jimenez-Rodriguez, Rosa M.; Patil, Sujata; Keshinro, Ajaratu; Shia, Jinru; Vakiani, Efsevia; Stadler, Zsofia; Segal, Neil H.; Yaeger, Rona; Konishi, Tsuyoshi; Shimada, Yoshifumi; Widmar, Maria; Wei, Iris; et al.
ABSTRACT: Tumor infiltrating lymphocytes (TIL), which represent host adaptive response to the tumor, were first identified at scanning magnification to select areas with the highest counts on hematoxylin and eosin slides, quantitated per high-power field (HPF), and analyzed for association with recurrence-free survival (RFS) in 848 patients. Highest TIL in a single HPF was analyzed as a continuous and categorical variable, and optimal cutoff analysis was performed to predict RFS. Highest TIL count in a single HPF ranged from 0 to 45, and the optimal cutoff for TIL high vs TIL low was determined to be ≥ 3 vs < 3 with a concordance probability estimate of 0.74. In the entire cohort, 5-year RFS was 90.2% (95% CI = 83.7–94.2) in TIL high compared to 78.9% (95% CI = 74.1–82.9) in TIL low (log rank P < .0001). TIL remained significant in the mismatch repair-proficient (pMMR) cohort where 5-year RFS was 94.6% (95% CI = 88.3–97.5) in TIL high compared to 77.9% (95% CI = 69.2–84.4) in TIL low ( P = .008). On multivariable analysis, TIL and AJCC Stage were independently associated with RFS in the pMMR cohort. Qualitatively in the pMMR cohort, RFS in Stage II TIL high patients was similar to that in Stage I patients and RFS in Stage III TIL high was similar to that in Stage II TIL low patients. Assessment of TIL in a single HPF using standard H&E slides provides important prognostic information independent of MMR status and AJCC stage.